2018
DOI: 10.1177/2053951718802321
|View full text |Cite
|
Sign up to set email alerts
|

Data in the smart city: How incongruent frames challenge the transition from ideal to practice

Abstract: This paper presents an analysis of interviews, focus groups and workshops with employees in the technical administration in the municipality of Copenhagen in the year after it won a prestigious Smart City award. The administration is interpreted as a 'most likely' to succeed in translating the idealised version of the smart city into a workable bureaucratic practice. Drawing on the work of Orlikowski and Gash, the empirical analysis identifies and describes two incongruent 'technological frames' that illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
(38 reference statements)
0
25
0
Order By: Relevance
“…In most cases, women are always concerned with the safety and personal security elements of transport. More so, several studies [35,51,57] indicated that better transportation systems have always contributed to people's quality of life in a given society. In this case, allowing women to participate in policymaking, especially on sustainable transport, has brought economic growth and efficient transport systems in most cities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, women are always concerned with the safety and personal security elements of transport. More so, several studies [35,51,57] indicated that better transportation systems have always contributed to people's quality of life in a given society. In this case, allowing women to participate in policymaking, especially on sustainable transport, has brought economic growth and efficient transport systems in most cities.…”
Section: Discussionmentioning
confidence: 99%
“…Copenhagen, being a smart city [35], obviously requires smart solutions to the ever-growing transportation demands from inhabitants [36]. Following this, the city deliberately planned to ease transportation while limiting traffic congestion through establishment of a complex bicycle lane system.…”
Section: Cycling For Sustainable and Smart Citiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kitchin [12] (p. 9) defines technocratic governance as the procedure by which "all aspects of a city can be measured and monitored and treated as technical problems that can be addressed through technical solutions." Thus, the aggregated use of digital data to monitor, surveil, and nudge citizens has resulted in an intrinsic version of the technocratic smart city [13][14][15], which pervasively bypasses the democratic accountability to which stakeholders are entitled. Despite these negative side effects, smart cities have remained the focus of urban policy and decision-makers worldwide, as a broad rubric for using the so-called stakeholder and citizen engagement practices orientated towards the management in such techno-deterministic-and more bluntly, less democratic-and, thus, further platformised urban realms [16][17][18].…”
Section: Introduction: Democratising the Technocratic Smart Citymentioning
confidence: 99%
“…The magnificent goals of smart cities include quality of life, sustainability, and development [1], which have already attracted a great deal of attention from researchers in an array of disciplines, such as urban planning [2][3][4], transportation [5][6][7], civil engineering [8], information science [9][10][11][12][13], surveying and mapping [14,15], commercial and logistics [16], energy [17,18], atmosphere and environment [19], society [20,21], tourists [22], governance [2,23], and industry in recent years. Although the proper definition of smart cities are still lacking [2], smart cities' goals are consistent to include smart living, smart people, smart environment, smart mobility, smart economy, smart governance [24], smart services, and smart infrastructure [25].…”
Section: Introductionmentioning
confidence: 99%